2010
DOI: 10.1121/1.3506351
|View full text |Cite
|
Sign up to set email alerts
|

The effect of native vowel processing ability and frequency discrimination acuity on the phonetic training of English vowels for native speakers of Greek

Abstract: The perception and production of nonnative phones in second language (L2) learners can be improved via auditory training, but L2 learning is often characterized by large differences in performance across individuals. This study examined whether success in learning L2 vowels, via five sessions of high-variability phonetic training, related to the learners' native (L1) vowel processing ability or their frequency discrimination acuity. A group of native speakers of Greek received training, while another completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 58 publications
6
51
3
Order By: Relevance
“…It is possible that earlier in development, auditory discrimination abilities play a unique role. For example, enhanced auditory discrimination skills seem to facilitate vowel learning for adults acquiring a second language; adults have presumably already developed a robust understanding of the role of pitch in language (Lengeris & Hazan, ). We propose that exceptionally strong pitch discrimination skills may be harmful, rather than helpful, for language acquisition during the first 2 years of life.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that earlier in development, auditory discrimination abilities play a unique role. For example, enhanced auditory discrimination skills seem to facilitate vowel learning for adults acquiring a second language; adults have presumably already developed a robust understanding of the role of pitch in language (Lengeris & Hazan, ). We propose that exceptionally strong pitch discrimination skills may be harmful, rather than helpful, for language acquisition during the first 2 years of life.…”
Section: Discussionmentioning
confidence: 99%
“…Other investigations into cross-linguistic speech perception have found that listeners’ L1 backgrounds influence identification and discrimination patterns (e.g., Ingram & Park, 1998), suggesting that patterns of assimilation to existing L1 categories determine performance (Flege, 2003). Iverson and Evans (2007; Lengeris & Hazan, 2010) have recently suggested that training doesn’t alter listeners’ phonetic categories but instead improves efficiency of categorization within the bounds of the existing L1 and L2 categories, highlighting the inability to change cue weightings over training as an indicator of unchanging category structure. If that is the case, it may be that something similar happens with immersion, where listeners do not fundamentally alter their category structure but instead become better at using their L1 and L2 categories to identify native and non-native speech sounds.…”
Section: 0 Discussionmentioning
confidence: 99%
“…The hypothesis that auditory processing may be a bottleneck for second language learning is supported by short-term training studies which have assessed auditory perception prior to asking participants to briefly learn a speech sound contrast from an unfamiliar language. These studies have found that rapid speech sound learning is linked to behavioural measures of auditory processing such as spectral (Wong & Perrachione, 2007;Lengeris & Hazan, 2010) and temporal (Kempe, Thoresen, Kirk, Schaeffler, & Brooks, 2012;Kempe, Bublitz, & Brooks, 2015) discrimination acuity, as well as greater white matter density and volume in left Heschl's gyrus (Golestani, Molko, Dehaene, LeBihan, & Pallier, 2007; and the robustness of neural encoding of speech (Chandrasekaran, Kraus, & Wong, 2011). Recently, we have shown that the robustness of neural encoding of speech is linked to English speech perception ability in native Japanese speakers (Omote, Jasmin, & Tierney, 2017) and to English speech production ability in native Mandarin Chinese speakers (Saito, Sun, & Tierney, 2018) living in the UK, suggesting that individual differences in auditory encoding may relate to L2 learning outside of the laboratory as well.…”
Section: Introductionmentioning
confidence: 99%